Galilean covariance and the Duffin-Kemmer-Petiau equation - De Montigny, M.; Khanna, F. C.; Santana, A. E.; Santos, E. S. [UNESP]; Vianna, J. D M (IOP Publishing, 2000)
We use a five-dimensional approach to Galilean covariance to investigate the non-relativistic Duffin-Kemmer-Petiau first-order wave equations for spinless particles. The corresponding representation is generated by five 6 × 6 matrices. We consider the harmonic oscillator as an example.